Long‐term nitrogen loading alleviates phosphorus limitation in terrestrial ecosystems. (1st July 2020) - Chen, Ji; van Groenigen, Kees J.; Hungate, Bruce A.; Terrer, César; van Groenigen, Jan‐Willem; Maestre, Fernando T.; Ying, Samantha C.; Luo, Yiqi; Jørgensen, Uffe; Sinsabaugh, Robert L.; Olesen, Jørgen E.; Elsgaard, Lars
Abstract: Increased human‐derived nitrogen (N) deposition to terrestrial ecosystems has resulted in widespread phosphorus (P) limitation of net primary productivity. However, it remains unclear if and how N‐induced P limitation varies over time. Soil extracellular phosphatases catalyze the hydrolysis of P from soil organic matter, an important adaptive mechanism for ecosystems to cope with N‐induced P limitation. Here we show, using a meta‐analysis of 140 studies and 668 observations worldwide, that N stimulation of soil phosphatase activity diminishes over time. Whereas short‐term N loading (≤5 years) significantly increased soil phosphatase activity by 28%, long‐term N loading had no significant effect. Nitrogen loading did not affect soil available P and total P content in either short‐ or long‐term studies. Together, these results suggest that N‐induced P limitation in ecosystems is alleviated in the long‐term through the initial stimulation of soil phosphatase activity, thereby securing P supply to support plant growth. Our results suggest that increases in terrestrial carbon uptake due to ongoing anthropogenic N loading may be greater than previously thought. Abstract : Current Earth System Models predict strong P limitation of plant productivity, based on the assumption that anthropogenic N enrichment shifts plant growth from N to P limitation. However, empirical evidence for P limitation following prolonged N additions is equivocal, and temporal variations in P limitation have not been systematically assessed. Using soil phosphatase activity as an indicator of P limitation, we show that N‐induced P limitation acclimates to long‐term N addition. This finding highlights the importance of plant and microbial adaptation strategies to control P availability. Absence of these strategies in models underestimates the potential of vegetation to slow climate change.